2020
DOI: 10.1136/bmjopen-2020-037546
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in prevalence and determinants of hypertension among adults: a cross-sectional survey of one rural village in Bangladesh

Abstract: ObjectivePrevention of mortality due to cardiovascular disease (CVD) through control of hypertension is a public health priority in Bangladesh. Our objective was to assess sex differences in prevalence and determinants of hypertension among adults in one rural area of Bangladesh.Study designCross-sectional.Setting and participantsFrom January 2014 to December 2015, we conducted a cross-sectional study of 2600 men and women aged ≥18 years located in one rural district of Bangladesh. We collected data on demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 22 publications
4
11
0
Order By: Relevance
“…Previous community‐based rural studies of Bangladesh also determined age as a predictor of both pre‐HTN and HTN. 14 , 15 Other Asian countries also reported similar findings of age and high BP in terms of pre‐HTN and HTN. 36 , 43 A previous Bangladeshi study showed a significant positive relationship between high BP and age, irrespective of gender.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Previous community‐based rural studies of Bangladesh also determined age as a predictor of both pre‐HTN and HTN. 14 , 15 Other Asian countries also reported similar findings of age and high BP in terms of pre‐HTN and HTN. 36 , 43 A previous Bangladeshi study showed a significant positive relationship between high BP and age, irrespective of gender.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies in Bangladesh also reported similar findings for pre‐HTN and HTN in rural settings about obesity. 14 , 15 , 16 However, in previous research, the association of central obesity (central fat distribution) measured using waist‐to‐hip ratio showed a stronger relationship with high BP than generalized obesity. 53 Regarding diabetes, our findings coincide with another rural study in Bangladesh.…”
Section: Discussionmentioning
confidence: 91%
“…Similar results were seen in India [37], Korea [38], and the United States [39]. However, recently, opposite results were seen in Bangladesh, showing a higher prevalence of hypertension among women [40]. Several sex-related determinants of hypertension (i.e., age, dietetic habits, education, BMI, glucose) have been identified as important moderators able to explain those differences.…”
Section: Discussionmentioning
confidence: 59%
“…Similar study conducted in Jiangsu also reported that women was negative associated with HRQoL among patients [18]. Compared with men, women were more likely to neglect their hypertension symptoms [38]. This limited treatment hypertension condition would make women more vulnerable to complications, which hinted that an inverse association between women and HRQoL was reasonable [39].…”
Section: Discussionmentioning
confidence: 69%